Opioids in COVID-19: Two Sides of a Coin - Palamim, Camila Vantini Capasso; Boschiero, Matheus Negri; Faria, Aléthea Guimarães; Valencise, Felipe Eduardo; Marson, Fernando Augusto Lima (Frontiers in Pharmacology, 2022)
Introduction: The treatment of most severe COVID-19 patients included the large-scale use of sedatives and analgesics – possibly in higher doses than usual – which was reported in the literature. The use of drugs that decrease mortality is necessary and opioids are important agents in procedures such as orotracheal intubation. However, these drugs seem to have been overestimated in the COVID-19 pandemic. We performed a review of the PubMed-Medline database to evaluate the use of opioids during this period. Results: Several positive points were found in the use of opioids in the COVID-19 pandemic, for instance, they can be used for analgesia in orotracheal intubation, for chronic pain management, and as coadjutant in the management of acute intensification of pain. However, high doses of opioids might exacerbate the respiratory depression found in COVID-19 patients, their chronic use can trigger opioid tolerance and the higher doses used during the pandemic might result in greater adverse effects. Unfortunately, the pandemic also affected individuals with opioid use disorder, not only those individuals are at higher risk of mortality, hospitalization and need for ventilatory support, but measures taken to decrease the SARS-CoV-2 spread such as social isolation, might negatively affect the treatment for opioid use disorder. In Brazil, only morphine, remifentanil and fentanyl are available in the basic health care system for the treatment of COVID-19 patients. Out of the 5,273,598 opioid units used in this period all over the country, morphine, fentanyl, and remifentanil, accounted for, respectively, 559,270 (10.6%), 4,624,328 (87.6%), and 90,000 (1.8%) units. In the COVID-19 pandemic scenario, positive points related to opioids were mainly the occurrence of analgesia, to facilitate intubation and their use as coadjutants in the management of acute intensification of pain, whereas the negative points were indiscriminate use, the presence of human immunosuppressor response and increased adverse effects due to higher doses of the drug. Conclusions: The importance of rational and individualized use of analgesic hypnotics and sedative anesthetics should be considered at all times, especially in situations of high demand such as the COVID-19 pandemic.